“Debate Guru”: Honing Public Speaking Skills Among Secondary School Students with AI Tutoring Systems - Nadan, Zachary; Goldberg, Nathan; Aliabadi, Roozbeh; Li, Shuhan (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
AI-supported tools have entered K-12 classrooms in recent years to reshape student learning and skill-building. We are particularly interested in AI’s application in literacy subjects, such as English, where students are expected to hone their critical thinking and public speaking skills through AI interactions. This report details the pilot implementation of Debate Guru, an AI-enhanced debate education platform, across two secondary schools with varying instructional contexts. Over the course of a summer school course, educators integrated Debate Guru in one of two ways: 1) by using Debate Guru’s complete curriculum; or 2) by combining platform resources with their own instruction such as a literary text. The pilot was implemented with approximately 50 students across Grade 8-11. Findings suggest significant increases in students’ confidence, argumentative reasoning, and engagement. Teachers reported high usability and strong pedagogical value, while students responded positively to interactive features and AI feedback integration. The pilot demonstrated preliminary usefulness and scalability of AI tutoring systems in debate classes. Future iterations can benefit from longitudinal studies, technical refinements, and school capacity-building to ensure greater generalizability of results and deeper knowledge acquisition.